O trabalho dos socorristas bombeiros militares: a experiência do reconhecimento social e da necessidade - Chadud, Reycilane Carvalho (2013)
This thesis aims to analyze the representations of workers participated in the activities of military rescue firefighter. This goal is justified by both the social need in the community for this task, as the intense public acceptance, even before the new structuring of the working world. The study was done in barracks in the cities of Goiânia-GO and São Paulo-SP. The initial assumption was that the research motivation for the activity of firefighters, it would give especially in emergency first aid for vocational motivations already orchestrated by his workers even before the inclusion in the workplace. This would characterize as positive representation of the profession, especially after a few years of effective work. The dissertation has as its starting point some observations on the changes in the country, the internal work environment of the barracks with the inclusion of this type of service to society, as well as the debate around the concept of professional identity, representation and social risk heroic rescue work that has accumulated in their work initiatives, mainly in the States concerned. The analysis part of the identity of some theoretical contributions that conceive social representation and professional identity as a result of the everyday processes of society and its social fund of knowledge about the activity of rescuers. From the interviews with workers, sought to build a characterization of rescuers, as well as their perceptions and assimilation toward work, both before its insertion, as their propensities for the future and the Institution. The analyzed data indicate significant differences with regard to the intentions and also the motivations of entry into the profession in the two cities, as well as the educational profile and age. The survey found a significant difference, arising from the possession educational factor difference in the highest and lowest degree of involvement with work as a primary source of vocation. Furthermore, it was possible to notice a difference in the way it views the identity of rescuers inside and outside the barracks, to provide subsidies that favor the question of "being" and "being a firefighter," as possible cases of aversion to activity, fruit of labor relations of psychological strain and physical, that most contribute to the formation of a collective identity.